Outputs of Reform Institutions in the Rehabilitation of Delinquents of the Labour Market: A field social study in the Juvenile Reform Department in Baghdad - Jawad Hanee, Alaa’; Shaker Mahdi, Majida (Al-Adab Journal, 2020)
The aim of this study concentrates on the following main question: how useful are those programs prepared within the reform institutions in meeting their needs towards the lab our market? Based on this question, 180 forms have been distributed to a random sample of juvenile delinquents who were placed in juvenile reform schools for their rehabilitation and reintegration into society within the reform institutions in Baghdad . Questionnaire, interviews and observation tools were used to collect information and data. The Questionnaire consists of many axes to measure the accuracy of the study variables. The first axis involves the primary data of the respondents; the second one contains the data of the reform institution and rehabilitation and the third axis includes the data of the training programs for delinquents and the labour market. In light of these axes, the tool was built and developed after presenting it in its initial form to nine experts of social sciences. The study targeted juvenile delinquents of (15-21years) in the juvenile reform department in Baghdad. The researcher relied on the social survey approach in identifying and processing the variables in order to analyses the questionnaire responses using some statistical techniques, such as ratios and frequency, the validity test, chi-square test for the relationship between variables, Cronbach’s alpha for reliability and other statistical methods to support the theoretical side.